2016
DOI: 10.1007/s11548-016-1510-4
|View full text |Cite
|
Sign up to set email alerts
|

Semiautomatic classification of acetabular shape from three-dimensional ultrasound for diagnosis of infant hip dysplasia using geometric features

Abstract: The proposed technique reduces the subjectivity of image-aided DDH diagnosis and could be useful in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Experts have been trying to develop new indicators, such as the 3D acetabular contact angle, contour α angle, and rounding index, for the accurate diagnosis of DDH 16,17 . Some researchers have also used 3D US to classify the shape of the acetabulum semiautomatically and used geometric features to diagnose DDH 18 . All of these factors promote the continuous development and application of 3D US.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experts have been trying to develop new indicators, such as the 3D acetabular contact angle, contour α angle, and rounding index, for the accurate diagnosis of DDH 16,17 . Some researchers have also used 3D US to classify the shape of the acetabulum semiautomatically and used geometric features to diagnose DDH 18 . All of these factors promote the continuous development and application of 3D US.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Some researchers have also used 3D US to classify the shape of the acetabulum semiautomatically and used geometric features to diagnose DDH. 18 All of these section by selecting the largest cross-section of the femoral head, which is relatively easy to find. It has been shown that the obtained measurement results are in good agreement with those of the Graf classification technique for the standard section.…”
Section: Discussionmentioning
confidence: 99%
“…ACA is measured as the angle between the summed point normals for the iliac wing surface and acetabular roof surface. 14 , 16 , 17 Mabee et al 16 reported significantly higher reliability and slightly higher diagnostic accuracy of ACA when compared to the conventional α angle. Apart from angularity, roundness of the acetabulum is considered during hip examination in most centres.…”
Section: Introductionmentioning
confidence: 99%
“…13 Various 2D and 3D indices of α angle, FHC, acetabular contact angle (ACA) and osculating circle radius (OCR), have been developed to aid interpretation of 3DUS (Figure 1). 1516,17 2D α angle and FHC indices were calculated semiautomatically from acetabular surface model in a similar manner to the Graf method and Morin and Harcke method, respectively. 11,1818 Their 3D versions extend these indices to slices with acetabulum in the 3DUS volume and report their average values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation